2018
DOI: 10.3389/fpls.2018.01473
|View full text |Cite
|
Sign up to set email alerts
|

Plant Growth-Promoting Rhizobacteria: Context, Mechanisms of Action, and Roadmap to Commercialization of Biostimulants for Sustainable Agriculture

Abstract: Microbes of the phytomicrobiome are associated with every plant tissue and, in combination with the plant form the holobiont. Plants regulate the composition and activity of their associated bacterial community carefully. These microbes provide a wide range of services and benefits to the plant; in return, the plant provides the microbial community with reduced carbon and other metabolites. Soils are generally a moist environment, rich in reduced carbon which supports extensive soil microbial communities. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
764
0
21

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 1,307 publications
(950 citation statements)
references
References 227 publications
15
764
0
21
Order By: Relevance
“…Previous results have shown that LBUM677 is able to solubilize phosphate, produce IAA-like compounds, ACC deaminase and siderophores (Novinscak and Filion 2018), which are all mechanisms that have previously been demonstrated to increase plant biomass (Compant et al 2005;Beauregard 2015;Backer et al 2018). The increase in seed, oil and SDA yields in B. arvensis reported in this study could be due in part to the benefits brought on by these mechanisms in LBUM677, or it could be due to other currently uncharacterized mechanisms of plant growth promotion by the bacterium.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…Previous results have shown that LBUM677 is able to solubilize phosphate, produce IAA-like compounds, ACC deaminase and siderophores (Novinscak and Filion 2018), which are all mechanisms that have previously been demonstrated to increase plant biomass (Compant et al 2005;Beauregard 2015;Backer et al 2018). The increase in seed, oil and SDA yields in B. arvensis reported in this study could be due in part to the benefits brought on by these mechanisms in LBUM677, or it could be due to other currently uncharacterized mechanisms of plant growth promotion by the bacterium.…”
Section: Discussionmentioning
confidence: 94%
“…; Beauregard ; Backer et al . ). The increase in seed, oil and SDA yields in B. arvensis reported in this study could be due in part to the benefits brought on by these mechanisms in LBUM677, or it could be due to other currently uncharacterized mechanisms of plant growth promotion by the bacterium.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Biofilm formation was synergistically enhanced in the consortium for two of the media tested (NB, Figure 2; TSB, Supporting Information Figure S2). In the past, most studies used single strains of Pseudomonas or Bacillus to study biofilm formation and bioprotection -see, for example, the reviews of Backer et al (2018) and Pandin et al (2017) -although the idea of using defined bacterial communities is not new (Lebeis et al, 2015;Xu, Jeffries, Pautasso, & Jeger, 2011). Nevertheless the number of studies investigating the biofilm formation and bioprotection mechanism of a bacterial consortium is still very limited and their practical use remains an agricultural goal (Mazzola & Freilich, 2016).…”
Section: Discussionmentioning
confidence: 99%